Overconfidence, Herding Behavior, dan Prinsip Syariah : Analisis Interdisipliner Behavioral Finance dalam Dinamika Pasar Modal Syariah - Muh. Syibawaih; M. Zaidi; M. Firdaus (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to interdisciplinary analyze the influence of overconfidence and herding behavior on the dynamics of the Islamic capital market, as well as examine the role of sharia principles as a moderating mechanism against investor behavioral bias. This study uses a Systematic Literature Review (SLR) approach with reference to the PRISMA guidelines to identify, select, and synthesize reputable scientific articles for the 2020-2025 period relevant to the theme of Islamic behavioral finance. The results of the study indicate that overconfidence increases trading intensity and risk exposure, while herding behavior amplifies short-term volatility and convergence of Islamic stock prices, especially during periods of market uncertainty. However, sharia principles, through screening mechanisms, prohibitions on riba and gharar, and strengthening ethical values ​​such as justice and responsibility, act as moderating variables that relatively reduce the destructive impact of these biases. These findings confirm that Islamic capital markets are not completely immune to behavioral distortions, but possess a normative-institutional framework that can strengthen market discipline. This research contributes to the development of Islamic behavioral finance by offering an integration of psychological and normative perspectives to explain Muslim investor behavior and its implications for the stability and efficiency of Islamic capital markets.